Utilizing Iron's Attractive Chemical and Magnetic Properties in Microrocket Design, Extended Motion, and Unique Performance. Issue 21 (10th April 2017) - Karshalev, Emil; Chen, Chuanrui; Marolt, Gregor; Martín, Aída; Campos, Isaac; Castillo, Roxanne; Wu, Tianlong; Wang, Joseph
Abstract : All‐in‐one material for microrocket propulsion featuring acid‐based bubble generation and magnetic guidance is presented. Electrochemically deposited iron serves as both a propellant, toward highly efficient self‐propulsion in acidic environments, and as a magnetic component enabling complete motion control. The new microrockets display longer lifetime and higher propulsion efficiency compared to previously reported active metal zinc‐based microrockets due to the chemical properties of iron and the unique structure of the microrockets. These iron‐based microrockets also demonstrate unique and attractive cargo towing and autonomous release capabilities. The latter is realized upon loss of the magnetic properties due to acid‐driven iron dissolution. More interestingly, these bubble‐propelled microrockets assemble via magnetic interactions into a variety of complex configurations and train structures, which enrich the behavior of micromachines. Modeling of the magnetic forces during the microrocket assembly and cargo capture confirms these unique experimentally observed assembly and cargo‐towing behaviors. These findings provide a new concept of blending propellant and magnetic components into one, toward simplifying the design and fabrication of artificial micro/nanomachines, realizing new functions and capabilities for a variety of future applications. Abstract : "All‐in‐one" iron‐based microrockets with efficient propulsion in acid, extended lifetime, facile magnetic guidance, heavy‐cargo pickup and release, and self‐assembly capability are demonstrated. Leveraging the intrinsic biocompatibility of iron with its multipurpose role in the microrocket design represents an important step toward wider in vivo use of micromotors.